IMPROVING THE SOFTWARE FOR DEVELOPING INFORMATION CULTURE IN STUDENTS (Universal International Scientific Journal, 2026)
In the age of information and knowledge, the intensification of the process of digital transformation, which covers all aspects of the life of modern society, makes the issue of developing information culture a very important issue in the formation of the intellectual and social potential of the new generation. Various forms and methods are used to form students studying at universities and higher educational institutions - people who are thirsty for knowledge, who can quickly master modern knowledge, who correctly understand freedom of information and use it rationally. In particular, innovative technologies and modern software tools play an important role in increasing information culture. As a result of the emergence of many new programs, information systems, and digital resources in the global information space, all areas of student life are increasingly connected with a wider flow of information.
Keywords: information culture, software, digital technologies, educational process, information security, learning platforms, electronic resources, modern programs, information management, knowledge development.